Production of waste soybean oil biodiesel with various catalysts, and the catalyst role on the CI engine behaviors - A?bulut .; Sathish T.; Kiong T.S.; Sambath S.; Mahendran G.; Kandavalli S.R.; Sharma P.; Gunasekar T.; Kumar P.S.; Saravanan R. (Elsevier Ltd, 2025)
The soybean oil wastes are disposed of after being used multiple times (maximum utilization) in the various food processing industries. Disposal of such waste are harmful to the environment and human. Hence, this investigation aims to use such wastes are used for producing alternate fuels for diesel engines. The biodiesel produced from the soybean waste cooking oil by transesterification process with different hybrid catalysts such as the membrane of Poly-acrylonitrile nanofibrous (MPANF), Alkyl-celite (AC), Iron oxide (IO-II) and Ni-doped ZnO (NDZ). The transesterification process variables like flow velocities varied from 0.3 to 1.5 mL/min and the reaction time varied from 15 to 75 h. The influence of such variables was investigated. The best two yields of waste soybean oil (BDWSBO) with the use of IO-II and AC catalysts respectively at 1.5 mL/min of flow rate at a 75-h reaction time, were considered for preparing further blends with diesel of 25 vol% and 50 vol% (Total 4 fuel varieties other than plain diesel). The test results revealed that a blend of 25 % diesel fuel with 75 % IO-II -used BDWSBO has 30.05 % BTE, which is nearer to diesel fuel (30.81 %). This blend has 17.96 % lesser smoke opacity than diesel fuel. Therefore, this 25 % diesel fuel with 75 % IO-II -used BDWSBO blend is recommended for higher production biodiesel and application in the IC engine as an alternate fuel without any modifications. ? 2023 Elsevier Ltd